An investigation of MWIR, AlInSb LEDs based on double heterostructures and multiple quantum wells - Ding, Y.; Meriggi, L.; Steer, M.; Bulashevich, K.; Thayne, I.; MacGregor, C.; Sorel, M.; Ironside, Charlie (Institute of Electrical and Electronics Engineers Inc., 2015)
Mid-mfrared LEDs based on AlInSb double heterostrucutre and multiple quantum well active regions have been simulated and investigated using the SimuLED software package from STR. The simulation results indicate that the double heterostrucutre and multiple quantum well active regions offer higher carrier injection efficiency and energy conversion. This translates into an output power and wall-plug efficiency that are three and two times higher, respectively, than a conventional homojunction active region.